A randomized comparative study to estimate the safety and effectiveness between laryngeal mask airway supreme and I-gel in patients undergoing elective surgeries - Kaushal Kabir,; Keshav Middha,; Arora KK,; Sharma, Aseem (Asian Journal of Medical Sciences, 2023)
Background: Supreme laryngeal mask airway (SLMA) and i-gel airway devices are second generation supraglottic airway devices (SAD) and are good alternatives to intubation during elective surgeries. Aims and Objectives: This study was conducted with the objective of comparing the two SAD with respect to ease of insertion, number of attempts of insertion, insertion time, ease of gastric tube insertion, accompanying hemodynamic changes, incidence of adverse effects like regurgitation, lip and dental trauma, post-operative sore throat, dysphagia, and hoarseness. Materials and Methods: This study was conducted at M.G.M. Medical College and M.Y. hospital, Indore. Eighty patients belonging to ASA class 1 or 2, with Mallampati grading 1 or 2, between age group of 18–60 years and with BMI <30 kg/m2 were selected for the study. After induction of anesthesia, one of the SAD’s (SLMA or i-gel) was inserted following randomization, and accordingly, the patients were divided into two groups of 40 each. Insertion parameters, hemodynamic, and respiratory parameters were noted. Patients were also observed for any possible complication at 1 h and 24 h postoperatively. Results: The Two groups showed no statistically significant difference in terms of demographic characteristics, insertion parameters, hemodynamic, or respiratory parameters (P>0.05). Postoperatively, no significant complications were observed in terms of dental injury, laryngospasm. Ease of gastric tube insertion was found to be more in SLMA group than i-gel and the difference was statistically significant (P=0.0057). Incidence of sore throat after 1 h was found to be more in SLMA group than i-gel group (P=0.048). Conclusion: There was no significant difference between SLMA and i-gel in terms of insertion characteristics and hemodynamic changes. Ease of gastric tube insertion was found to be significantly more in SLMA group than i-gel. Incidence of post-operative sore throat at 1 h was more with SLMA as compared to i-gel.